2009
DOI: 10.3163/1536-5050.97.3.006
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Medical Library Association research agenda: methodology and final results from a consensus process

Abstract: The modified delphi method accomplished its desired survey and consensus goals. Future survey and consensus processes will be revised to generate more initial questions and to distill a larger number of ranked prioritized research questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…They identified a gap between those questions being asked by library and information practitioners and those being addressed by researchers. A 2011 study (Eldredge, Ascher, Holmes, & Harris, 2012) identified the top-ranked research questions specifically for the medical library profession building on a previous study (Eldredge, Harris, & Ascher, 2009) but upgrading the methodology to improve answerability. A previous study has taken the "demand-supply chain" for EBLIP question-answering further by asking "what studies do practitioners actually find useful?"…”
Section: Literature Reviewmentioning
confidence: 99%
“…They identified a gap between those questions being asked by library and information practitioners and those being addressed by researchers. A 2011 study (Eldredge, Ascher, Holmes, & Harris, 2012) identified the top-ranked research questions specifically for the medical library profession building on a previous study (Eldredge, Harris, & Ascher, 2009) but upgrading the methodology to improve answerability. A previous study has taken the "demand-supply chain" for EBLIP question-answering further by asking "what studies do practitioners actually find useful?"…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, libraries have been slow in developing a research agenda focused on their own discipline [7].…”
Section: Brief Communication: Mcgowanmentioning
confidence: 99%
“…The intention was very much that "a problem shared is a problem halved" with colleagues often being able to suggest potential solutions that were not within the immediate view of the one generating the original issue. Finally Jonathan Eldredge shared with participants published examples, from the Research Section of the Medical Library Association (Eldredge et al, 2009) and the Swedish Library Association (Maceviciute & Wilson, 2009), of recent Delphi exercises on research priorities. It was suggested that similar methods might be usefully transferred and adopted, while recognising that the focus of the exercise in the Caribbean had been on impediments to evidence based library and information practice (i.e., related to implementation) and not on research priorities per se.…”
Section: In Twenty Hund-er-ed and Ten A Voyage Of Discovery Took Placmentioning
confidence: 99%